Converting spent tea leaves to electrode for energy storage application - Woo, Meng San (2019)
This project examines the feasibility of converting spent tea leaves into activated carbon via the chemical activation process for energy storage application. The activated carbon produced is a potential electrode material as compared to the commercially used TF6 Bipolar graphite plate in Vanadium Redox Flow Battery (VRFB) application. Orthophosphoric acid (H3PO4) was used as the activation reagent with the spent tea leaves at impregnation ratios of 1:1, 1:3 and 1:5. 6 samples were generated, 3 of them were generated from the conventional chemical activation procedure whereas the other 3 were generated with hydrothermal processes with chemical activation. Activated Carbon Characterisation showed better results for samples 1-3 as compared to samples HT4-HT6. However, both the Cyclic Voltammetry analysis and Electrochemical Impedance Spectra analysis showed slightly inferior electrochemical performance as compared to the Tf6 bipolar plate. Hence, further improvements are required to ensure that it is feasible to convert spent tea leaves into activated carbon via the chemical activation process to be used as an electrode for the VRFB energy storage application.